In debt but still happy? Examining the relationship between homeownership and life satisfaction - Sebastian Will; Timon Renz (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
We investigate the relationship between homeownership and life as well as housing satisfaction. Using panel data from Germany, we find that compared to renting, owning a home positively impacts housing satisfaction. Contrarily, we find no significant effects on life satisfaction in the long-term. Analysing short-term effects in an event-study design, we show that both life and housing satisfaction anticipate the event and adapt shortly after. Debt-free buyers, however, do not experience anticipation or adaptation effects at all. Comparing outright homebuyers to debt-financing owners, we show that having a real estate loan impacts homeowners' life satisfaction negatively. Paying off a loan does not differently affect the housing satisfaction of both types of buyers. We conclude that the negative effect of loan payments on life satisfaction offsets the positive impact of homeownership.
Keywords: D15; I31; R20; 330; subjective well-being; homeownership; household finances; financial burden; adaptation; housing satisfaction